Can Cooperatives Change The Standard Living of Youth? - Fajar Meiyanti; Asep Kurniawan; Icih Icih; Muhammad Muaz Bin Zainudin (Gorontalo State University, 2023)
Typical of social economy employees focus on social good rather than economic gain. They prefer to work in a sector that prioritizes satisfaction and makes them feel valued. Besides that, youth prefer to work in large places that provide greater welfare for them too. So usually working in Socially oriented businesses is made the second choice or next choice by youth. Some countries have policies to engage youth in Cooperatives. Youth represent the most important group among the working-age population. But then can cooperatives enterprise, as socially-oriented businesses, can provide and change the standard of living of youth? What motivates youth to engage in the socially oriented businesses?. This article examines field data from youth employees at cooperative members in Subang and Selangor. A survey was conducted by interview, observation and documentation study. According to the findings, now day cooperatives and their networks can change standard living of youth, but not only about it, cooperative provide an expanded learning space for youth, although there is differentiation by age, education and type of cooperative. The results of this study can attract the attention of youth to choose cooperatives as a new way to motivate youth to change their standard of living through cooperatives and learn a lot about business attitudes from this socially oriented business.